Scale‐dependent patterns and drivers of plant diversity in steppe grasslands of the Central Alborz Mts., Iran. (23rd April 2021) - Talebi, Amir; Attar, Farideh; Naqinezhad, Alireza; Dembicz, Iwona; Dengler, Jürgen
Abstract: Questions: Which are the main environmental drivers of plot scale alpha‐diversity and beta‐diversity in arid steppes? Do they vary between functional groups and across grain sizes? Location: Central Alborz Mts., N Iran. Methods: We sampled vascular plants in 23 nested‐plot series with nine grain sizes from 0.0001 m 2 to 1, 000 m 2 and 334 25‐m 2 vegetation plots in different vegetation types of natural dry steppe grasslands. To assess beta‐diversity, we calculated overall and local z ‐values of species–area relationships modelled with the power function. As potential drivers of species richness and z ‐values, we used topographic, edaphic and climatic variables as well as management types. Generalised linear models (GLMs), and generalised linear mixed‐effect models (GLMMs) if spatial autocorrelation occurred, were used in a multi‐model inference framework to build statistical models. Results: Mean annual temperature was the most important predictor for total species richness and richness of functional groups across grain sizes, with a unimodal relationship for grains of 25–100 m 2, but mostly increasing for finer grain sizes. Precipitation of the driest month and cover of gravel were influential drivers at the smallest grains. The explanatory power of regression models increased towards larger grain sizes. The overall z ‐values showed a high positive relationship with precipitation of the driest month, mean annual temperature and mean soil depth. Conclusions: Related to our more than 3, 000‐m elevational gradient, mean annual temperature (highly negatively correlated with elevation) was the most influential and consistent driver across functional groups and grain sizes with mostly unimodal relationships for alpha‐diversity and a positive effect on beta‐diversity. Findings for other drivers were less consistent, and overall the explained variance of our models was relatively low, calling for additional studies to determine whether in the arid grasslands of Iran stochasticity is just higher or there are additional important variables. Abstract : In a 3, 000‐m elevational gradient of Iranian mountains, species richness of vascular plants was recorded across nine spatial grain sizes and for functional groups. Mean annual temperature (highly negatively correlated with elevation) was the most influential and consistent driver across functional groups and grain sizes with mostly unimodal relationships for alpha‐diversity and a positive effect on beta‐diversity.